THE IMPACT OF IMPLEMENTING FINANCIAL RISK MANAGEMENT ON PROFITABILITY AND COMPANY VALUE COMPARATIVE STUDY BETWEEN BUMN AND PRIVATE COMPANIES IN INDONESIA - Bambang Hermawan; Miftahil Miftahil; Lika Yulia (Adisam Publisher, 2025)
This research aims to analyze the impact of implementing financial risk management on profitability and company value, with a focus on comparative studies between State-Owned Enterprises (BUMN) and private companies in Indonesia. Through a comprehensive literature review, this study explores various aspects of financial risk management and their impact on company performance. The method used in this research is systematic literature analysis, utilizing secondary sources such as scientific journals, company financial reports and other official publications. The data collected covers the 2010-2020 period, involving samples from 50 state-owned companies and 100 leading private companies in Indonesia. The research results show that the implementation of financial risk management has a significant positive impact on profitability and company value, both in BUMN and private companies. However, there are differences in the level and characteristics of the impact. Private companies tend to show a faster increase in profitability, while state-owned companies experience a more stable increase in company value in the long term. This study also reveals that the effectiveness of implementing financial risk management is influenced by factors such as ownership structure, government regulations, and organizational culture. SOEs face unique challenges related to political and bureaucratic interference, while private companies are more flexible but sometimes limited in terms of resources. In conclusion, this research provides valuable insight into the importance of financial risk management in improving company performance in Indonesia. These findings can be a reference for policy makers, company managers and investors in understanding the dynamics of financial risk management in the public and private sectors.